Comparison of biological features between severely immuno-deficient NOD/Shi-scid Il2rg(null) and NOD/LtSz-scid Il2rg(null) mice - Nagatani, Mariko (Exp Anim, 2019)
Biological background data up to 11 weeks of age and tumorigenic susceptibility to xenotransplantation with HeLa cells were compared between severely immuno-deficient NOG and NSG mice. The body weight was lower in NOG mice than in NSG mice. Severe depletion of peripheral blood lymphocytes and lymphoid hypoplasia that are well-known characteristics of these mice were equally observed. No lymphoproliferative lesions developed in any mouse of either strain. The occurrence of ectopic exocrine gland and cyst was a common finding in the thymus of both strains. In addition, minimal spongiotic change was observed in the medulla oblongata and spinal cord in both strains, and its incidence in female NOG mice was a little higher than that in NSG mice. In the adrenal, subcapsular cell hyperplasia that is known as an age-related change in non-genetically modified mice developed earlier and its incidence was higher in NSG mice than in NOG mice. The development of female genital organs of NOG mice was slightly retarded in comparison with that of NSG mice. To evaluate tumorigenic susceptibility to xenotransplantation, female mice were implanted in the dorsal subcutis with 1×10(3) to 1×10(6) cells/head of HeLa cells, and were checked up to 16 weeks after implantation. As a result, there was no significant strain difference on tumor formation rate and tumor volume. In conclusion, the present study clearly demonstrated that NOG and NSG mice showed no distinct strain differences in either biological features or biological disadvantages.